Mixed income housing development effects on surrounding property values : a city of Johannesburg case study - Mangwagape, Boitumelo (My University, 2017)
Mixed income housing models and inclusionary housing policy are among the leading solutions used internationally to foster inclusion and achieve restructuring (Huang 2015; Tajani and Morano 2015; Klug et al, 2013; (Onatu, 2010). The focus of this research is on Mixed Income Housing (MIH) developments as an alternative to the mass Reconstruction and Development Progamme (RDP) roll out. The myths and facts on the benefits of mixed income housing developments are debated in literature. The benefits (or perceived benefits) of mixed developments include a positive social impact and addressing the culture of poverty, a concept that states a concentration of poor households further enable negative behaviour such as drug abuse and joblessness (Landman, 2012) (Brophy and Smith, 1997). The benefits and myths have yet to prove that in the South African context. Low income housing and mixed income housing projects are argued to impact the surrounding property values. The study analysed the impact of the mixed income housing (MIH) development Cosmo City, located in the City of Johannesburg, on the surrounding single stand residential property values seen through the purchase prices of houses in the market. The study uses hedonic modelling to carry out the analysis. Three (3) variables are included in the model, purchase price as the dependent variable and the two (2) independent variables; municipal assessed values and distance from the MIH. The main variable of interest is the Distance from the MIH, as it gives indication of whether properties closer to Cosmo City actually has lower property prices (i.e. the purchase price) than those located farther away. This variable was found to be statistically significant with the expected positive sign, thus confirming that the farther a property is located from the MIH the higher the purchase price. The remaining independent variable, Municipal Assessed Value, is also found to be statistically significant. However, when outliers were excluded this variable became statistically insignificant. The model has a strong predictive power. For every 1 unit increase of the Municipal Assessed Value (X1) the purchase price increases by 0.00001398% (i.e. 0.0000001398 *100); and for every 1 unit increase of Distance from MIH the purchase price increases by 0.1% (i.e. 0.001 * 100).